Collective Bargaining Agreement University of Delaware and American Association of University Professors University of Delaware Chapter - Delaware Univ., Newark; Delaware Univ., Newark ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This collective bargaining agreement is between the University of Delaware and the American Association of University Professors, University of Delaware Chapter. Articles cover agreement, purpose, recognition, AAUP membership, AAUP representatives and privileges, bargaining unit membership, union responsibilities, grievance procedure, personnel benefits, nondiscrimination, faculty workload, salaries, totality of agreement, precedence of laws, maintenance of practices, term of agreement, and effective date. (MJM)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Collective Bargaining; Contracts; Fringe Benefits; Grievance Procedures; Higher Education; Negotiation Agreements; Teacher Salaries; Teaching Load; Universities; Working Hours; University of Delaware; American Association of University Professors